Performance of Conventional and Sustainable Index in Pre and During the COVID-19 Pandemic : A Comparative Analysis - Kaur Makkar, Manpreet; Ghayas, Atif; Gupta, Nitin (Indian Journal of Finance, 2023)
Purpose : There has been a significant increase in the demand for ESG (environmental, social, and governance) investment by investors in recent years. Investors are recognizing that companies that prioritize ESG factors in their operations are more likely to be sustainable and resilient in the long term. The purpose of this study was to examine whether the ESG-responsible firms are performing better than the other firms in the pre-COVID and during the COVID periods. The paper also tried to investigate the impact of COVID-19 cases on the index movement. Methodology : The study employed the descriptive analysis on the financial data of NSE NIFTY 500 and NIFTY 100 Enhanced ESG index. The EGARCH model was applied to estimate the effect of COVID-19 on the volatility of the NIFTY 100 Enhanced ESG index. Findings : The results showed that there was no leverage effect in the ESG index in both periods. That means that the ESG Index can act as a cushion during the pandemic period. The ESG Index outperformed the conventional market index, thus acting as a COVID-19 safe asset class. This gives an opportunity to investors and fund managers to diversify their risk by acting sustainably responsible for society. Practical Implications : This study compared the performance of ESG-indexed firms with that of other firms in the pre-COVID and during COVID time period to check whether there was any difference between them. This study provided empirical evidence for practitioners, policymakers, and academicians in support of ESG investment as it showed that the ESG Index performed better than the conventional index during the COVID period. Originality : This study used secondary data to study the performance of the EGS firms in the pre and during COVID period in order to compare with the other firms. In the context of India, this study may be the first one to compare the performance of the ESG firms with the normal firms in the pre and during the COVID period.